Voltaire's Russia - Wilberger, C (Voltaire Foundation, 2017)
Introduction I. France and Russia, 1700-1750 II. Voltaire, historian of Russia: i. The background III. Voltaire, historian of Russia: ii. the concepts IV. Voltaire's personal contacts with Russia V. Voltaire and Catherine the great VI. Russia: fact, fiction and formulae VII. The debate: Voltaire versus Rousseau VIII. The debate: philosophes, westernizers and Slavophiles Conclusion Bibliography